Biological and Physicochemical Studies of Oleyl Oleate as an Active Agent to be Applied in Cosmetic Formulation. - Fadhlin Hasya Shaiful Bahri; Salina Mat Radzi; Nur Amalina Mohd Amin; Maryam Mohd Rehan; Nurul Jannah Abdul Rahman (UiTM Press, Universiti Teknologi MARA, 2026)
Tier 3- Indexed by MyCite